2010
DOI: 10.1108/09654281011068522
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' perceptions of the words “health” and “happy”

Abstract: Purpose -The shared language of youth includes understandings of concepts that can be different from those of adults. Researchers, in their efforts to explore and illuminate the health behaviours and decision-making processes of young people, use generic terms in their data collecting protocols. This study aims to explore what adolescents understand by the words "healthy" and "happy". Design/methodology/approach -Semi-structured interviews were conducted in three post-primary schools with 31 students aged 12 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
1
6
0
2
Order By: Relevance
“…These findings share similarities with the few studies that have also incorporated children's own conceptualisations, for example Nic Gabhainn and Sixsmith (2006) revealed that people that were loved, food and drink, animals and pets, and sleep were important to children's happiness, findings which overlap with O'Higgins et al.'s. (2010) study of 12‐ to 13‐year olds that family and friends were integral to their happiness. Chaplin's (2009) investigation into what makes children and adolescents happy revealed five themes: people and pets, achievements, material things, hobbies and sports, and Backman's (2016) study showed that young people associated happiness with relationships, positive behaviours and school learning.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings share similarities with the few studies that have also incorporated children's own conceptualisations, for example Nic Gabhainn and Sixsmith (2006) revealed that people that were loved, food and drink, animals and pets, and sleep were important to children's happiness, findings which overlap with O'Higgins et al.'s. (2010) study of 12‐ to 13‐year olds that family and friends were integral to their happiness. Chaplin's (2009) investigation into what makes children and adolescents happy revealed five themes: people and pets, achievements, material things, hobbies and sports, and Backman's (2016) study showed that young people associated happiness with relationships, positive behaviours and school learning.…”
Section: Discussionsupporting
confidence: 81%
“…However, research that has begun to ask young people about their conceptualisations of happiness have illustrated that this is not the case. For example, O'Higgins, Sixsmith, and Nic Gabhainn (2010) explored young adolescents' interpretations of the words ‘healthy’ and ‘happy’, drawing on a grounded theory approach utilising semi‐structured interviews. Emerging themes revealed that happiness was broadly associated with doing things and being with people.…”
Section: Conceptualising Happinessmentioning
confidence: 99%
“…In terms of energy expenditure, children referred to being active outdoors and “fresh air” as being healthy, and the perceived consequences of watching too much television. Previous research has shown adolescent children also make reference to fresh air when discussing health (O'Higgins et al , 2010). A similar perception of healthiness has been found for younger and older children.…”
Section: Discussionmentioning
confidence: 99%
“…31 resultados, dos quais um trabalho, com adolescentes, tratou de percepções sobre as palavras saúde e felicidade (O'Higgins, Sixsmith & Gabhainn, 2010). O'Higgins et al (2010) entrevistaram 31 adolescentes (16 rapazes e 15 moças) de 12 e 13 anos de idade, sobre suas percepções para saúde e para felicidade.…”
unclassified
“…O'Higgins et al (2010) entrevistaram 31 adolescentes (16 rapazes e 15 moças) de 12 e 13 anos de idade, sobre suas percepções para saúde e para felicidade. A entrevista abordou a felicidade com questões como "o que te faz feliz?…”
unclassified